2017
DOI: 10.1186/s12885-017-3341-2
|View full text |Cite
|
Sign up to set email alerts
|

Oligometastases from prostate cancer: local treatment with stereotactic body radiotherapy (SBRT)

Abstract: BackgroundThe impact of local tumor ablative therapy in oligometastasized prostate cancer (PC) is still under debate. To gain data for this approach, we evaluated oligometastasized PC patients receiving stereotactic body radiotherapy (SBRT) to bone metastases.MethodsIn this retrospective study, 15 oligometastasized PC patients with a total of 20 bone metastases were evaluated regarding biochemical progression-free survival (PSA-PFS), time to initiation of ADT, and local control rate (LCR). Three patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 28 publications
5
64
0
2
Order By: Relevance
“…High local control rates are reported in literature in this setting. Ahmed et al and Habl et al, observed a similar 100% of local control when treating 17 and 15 patients respectively. Muacevic et al .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…High local control rates are reported in literature in this setting. Ahmed et al and Habl et al, observed a similar 100% of local control when treating 17 and 15 patients respectively. Muacevic et al .…”
Section: Discussionmentioning
confidence: 81%
“…Our results are consistent with those published by other authors. For example Habl et al reported that ADT had no impact on PFS, time to initiation of ADT, or to intensification of systemic therapy. Also Jereczek‐fossa et al demonstrated that time to progression after SBRT for nodal metastases was similar whether androgen deprivation was added or not (11 vs 10 months).…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion reasons with references are listed in Data S2. Finally, 14 articles were selected for data extraction and subsequent qualitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…One randomized controlled trial was found, but it did not meet all the eligibility criteria, so it was not included in the qualitative analysis . Thirteen articles were single‐arm case series/cohort studies, and one case–control series, with five (36%) prospective and nine (64%) retrospective researches . Median follow‐up period varied from 10.2 to 36.6 months (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation